Comparative proteomic analysis of different developmental stages of swamp buffalo testicular seminiferous tubules. (13th August 2017) - Zhang, P‐F; Huang, Y‐L; Fu, Q; Chen, F‐M; Lu, Y‐Q; Liang, X‐W; Zhang, M
Contents: With ageing, many protein components change markedly during mammalian spermatogenesis. Most of these proteins have yet to be characterized and verified. Here, we have employed two‐dimensional electrophoresis coupled to tandem mass spectrometry to explore the different proteins from pre‐pubertal, pubertal and post‐pubertal swamp buffalo testicular seminiferous tubules. The results showed that 25 protein spots were differentially expressed among developmental stages, and 13 of them were successfully identified by mass spectrometry. Of which four proteins were up‐regulated and three proteins were down‐regulated with age, and the remaining six proteins were fluctuated among developmental stages. Bioinformatics analysis indicates that these proteins were probably related to cellular developmental process (53.8%), cell differentiation (53.8%), spermatogenesis (15.4%), apoptotic process and cell death (30.8%). Expression profiles of calumenin (CALU) and galectin‐1 (LGALS1) were further verified via Western blotting. In summary, the results help to develop an understanding of molecular mechanisms associated with buffalo spermatogenesis.